The effect of inter-laboratory variability on the protein:creatinine (UPC) ratio in canine urine. Issue 1 (April 2015) - Rossi, G.; Bertazzolo, W.; Dondi, F.; Binnella, M.; Gruarin, M.; Scarpa, P.; Paltrinieri, S.
Highlights Inter-laboratory variability may affect the urine protein:creatinine (UPC) ratio. We measured the UPC ratio in the same canine samples in three different laboratories. UPC ratio was significantly different most likely due to different methods or instruments. Despite this, the concordance in classifying proteinuric dogs was very good. Inter-laboratory variability may affect patient monitoring during follow up.